Muslims in social media discourse: Combining topic modeling and critical discourse analysis. (September 2016) - Törnberg, Anton; Törnberg, Petter
Abstract: This article combines topic modeling and critical discourse analysis to examine patterns of representation around the words Muslim and Islam in a 105 million word corpus of a large Swedish Internet forum from 2000 to 2013. Despite the increased importance of social media in the (re)production of discursive power in society, this is the first study of its kind. The analysis shows that Muslims are portrayed in the forum as a homogeneous outgroup that is embroiled in conflict, violence and extremism: characteristics that are described as emanating from Islam as a religion. These patterns are strikingly similar to – but often more extreme versions of – those previously found in analysis of traditional media. This indicates that, in this case, the internet forum seems to serve as an "online amplifier" that reflects and reinforces existing discourses in traditional media, which is likely to result in even stronger polarizing effects on public discourses. Highlights: Combines topic modeling and critical discourse analysis. Analyzes the representation of Muslims and Islam in social media over time. Shows that Muslims are portrayed as a homogenous outgroup, embroiled in conflict, violence, extremism. The forum serves as an 'online amplifier', reflecting and reinforcing discourses in traditional media.